2007
DOI: 10.1007/s11103-007-9182-7
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis EIN2 modulates stress response through abscisic acid response pathway

Abstract: The nuclear protein ETHYLENE INSENSITIVE2 (EIN2) is a central component of the ethylene signal transduction pathway in plants, and plays an important role in mediating cross-links between several hormone response pathways, including abscisic acid (ABA). ABA mediates stress responses in plants, but there is no report on the role of EIN2 on plant response to salt and osmotic stresses. Here, we show that EIN2 gene regulates plant response to osmotic and salt stress through an ABA-dependent pathway in Arabidopsis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 58 publications
6
116
1
2
Order By: Relevance
“…The aux1-7 mutation in this gene confers both auxin and ethylene resistance (Pickett et al, 1990). In addition to its role as a central component of the ethylene signal transduction pathway (Alonso et al, 1999;An et al, 2010), EIN2 also functions as a cross-link node in ethylene and other phytohormone signaling pathways (Ghassemian et al, 2000;Wang et al, 2007). We found that the ein2-1 seedlings also exhibited insensitivity to exogenous IAA (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…The aux1-7 mutation in this gene confers both auxin and ethylene resistance (Pickett et al, 1990). In addition to its role as a central component of the ethylene signal transduction pathway (Alonso et al, 1999;An et al, 2010), EIN2 also functions as a cross-link node in ethylene and other phytohormone signaling pathways (Ghassemian et al, 2000;Wang et al, 2007). We found that the ein2-1 seedlings also exhibited insensitivity to exogenous IAA (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…[13][14][15][16][17] We analyzed the effect of AtMBF1 mutations on seed dormancy of abc-seeds and compared with ein3-1 mutant and abc-complemented with AtMBF1c gene overexpression (abc-+c).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Ein 2 null mutant is also supersensitive to both salt and osmotic stress conditions. 15 All these data suggest that a functional ethylene signal transduction pathway is necessary to fully develop several ABA responses. As we commented before there are evidences that MBF1 genes positively regulate ethylene signaling pathway.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the interaction between different hormones also needs to be considered, and several genetic mutants have been isolated that may help clarify the effect of hormones on anthocyanin biosynthesis. For example, high ABA levels in the ein2 mutant might be responsible for the high anthocyanin accumulation in these plants, demonstrating the dual regulation of ABA and ethylene signaling (Wang et al, 2007). New screening strategies coupled with proteomic and genomic techniques might further clarify the regulation of anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%